2012
DOI: 10.5144/0256-4947.2012.343
|View full text |Cite
|
Sign up to set email alerts
|

A molecular analysis of familial Mediterranean fever disease in a cohort of Turkish patients

Abstract: BACKGROUND AND OBJECTIVESFamilial Mediterranean fever (FMF) is an autosomal recessive disorder caused by mutations in MEFV gene, which encodes pyrin. FMF is especially prevalent among Turks, Armenians, non-Ashkenazi Jews, and Arabs. The aim of this study was to determine the frequency and spectrum of 12 MEFV mutations of these patients and any genotype-phenotype correlation in this large Turkish group.DESIGN AND SETTINGA retrospective study at Erciyes University Medical Faculty, from January 2007 to June 2009.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In trials conducted in Turkish population, the most common mutations were reported as M694V, E148Q, M680I and V726A [ 8 ]. The last ten years have seen much research into the effect of particular genetic mutations on clinical findings [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In trials conducted in Turkish population, the most common mutations were reported as M694V, E148Q, M680I and V726A [ 8 ]. The last ten years have seen much research into the effect of particular genetic mutations on clinical findings [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hot spots of the FMF-causing MEFV variants were found on exon 2, at position 148, and on exon 10, at positions 680 and 694 [39,40]. In Turkey, the most frequent mutations are M694V, E148Q, M680I, and V726A [41]. In the Israeli community, the common mutation for non-Ashkenazi Jews is M694V (76.8%) [42] and E148Q for Ashkenazi Jews [43], whilst V726A is the most encountered mutation among Arabs.…”
Section: Genetics and Genotype-phenotype Correlationsmentioning
confidence: 99%
“…The MEFV mutations directly affect pyrin protein activity by disrupting the balance between different inflammation factors, which may cause pain and fever in the chest, abdomen, and joints [6]. To date, mutations reported from different populations for FMF include Jewish, Armenian, Turkish, and Arab people with different frequencies [7]. From reported changes in the MEFV, five missense mutations namely E148Q, M694I, M694V, M680I, and V726A count as the most common reported mutations [8,9].…”
Section: Introductionmentioning
confidence: 99%